2010
DOI: 10.1186/1471-2334-10-253
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the treatment of acute rotavirus diarrhoea. A randomized, double-blind, controlled trial using two different probiotic preparations in Bolivian children

Abstract: BackgroundEvidence suggests that probiotics reduce rotavirus diarrhoea duration. Although there are several probiotic strains potentially useful, daily practice is often limited by the type and number of products locally available. In general, information about combined products is scarce. In this study we compare the effect of two probiotic products in the treatment of diarrhoea in children less than 2 years of age.MethodsA Randomized double-blind controlled clinical trial in children hospitalized for acute r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 29 publications
4
117
2
4
Order By: Relevance
“…SB has known positive effects on reduction of enteric pathogens of pigs including Escherichia coli (Lessard et al, 2008;Collier et al, 2011), and in human studies C. difficileassociated disease, and rotavirus infection (McFarland, 2006;Grandy et al, 2010); however, we found no evidence of such effects (data not shown). Not all diarrhoea is caused by infectious agents; thus, the significant reduction in diarrhoea in this study, related to SB administration, could be due to the physiological effects of SB improving osmotic balance.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…SB has known positive effects on reduction of enteric pathogens of pigs including Escherichia coli (Lessard et al, 2008;Collier et al, 2011), and in human studies C. difficileassociated disease, and rotavirus infection (McFarland, 2006;Grandy et al, 2010); however, we found no evidence of such effects (data not shown). Not all diarrhoea is caused by infectious agents; thus, the significant reduction in diarrhoea in this study, related to SB administration, could be due to the physiological effects of SB improving osmotic balance.…”
Section: Discussioncontrasting
confidence: 55%
“…boulardii is a non-pathogenic, non-colonising, yeast. Several studies have shown that, in humans, SB is an efficacious and safe probiotic, which has proven efficacy against some enteric diseases including, but not limited to, Clostridium difficile-associated disease and rotavirus diarrhoea (McFarland, 2006;Grandy et al, 2010;McFarland, 2010). Data on the effect of SB on neonatal porcine health are limited, possibly because of practical limitations of administration to individual neonates commercially; however, studies have demonstrated that SB supplementation improves growth in post-weaning pigs (Bontempo et al, 2006;Le Bon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that there is insufficient evidence to recommend L. acidophilus strain LB for treating diarrhea in children (24). Some studies also examined the effect of AGE treatment using other Lactobacillus species, some Bifidobacterium species, Streptococcus thermophilus, and other probiotics (25)(26)(27)(28). However, there is not enough evidence to recommend these probiotics for routine use in AGE (6).…”
Section: Placebo Groupmentioning
confidence: 99%
“…The discovery of Lactic Acid Bacteria (LAB) in the middle of the nineteenth century confirmed the interest in microorganism and since then many people have concluded that dairy fermented by lactobacillales provide numerous benefits to our health [2].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of a symbiotic relationship between bacteria and humans awoke the curiosity of seeing the bacteria as potentially beneficial rather than pathogenic [2].…”
Section: Introductionmentioning
confidence: 99%